A difference that is not a difference - Beaumont Enid
This symposium illustrates a serious problem. There has been a great deal of fragmentation in the field of public administration in the last two decades. For three decades, from the 40's through some of the 70's public administration was able to encompass many diverse approaches within its boundaries. However, dissatisfaction with traditional public administration content, methodology, incrementalism, and administrative management that have separated themselves from public administration. The desire for separateness is seen in changed names of academic programs and degrees, different course content and separate professional associations. The symposium was designed to try to stimulate debate and discussion
Keywords: Management; Policy Analysis; Public Policy -- Education; Public Administration